Insulin resistance and β-cell dysfunction in individuals with normal glucose tolerance but elevated 1-h post-load plasma glucose - Nie, Qianwen; Jin, Xue; Mu, Yahui; Huang, Youyuan; Dong, Aimei (Frontiers in Endocrinology, 2025)
ObjectiveDiabetes and its complications impose a significant burden on public health, necessitating early identification and intervention, yet current prediabetes diagnostic criteria may not fully capture all high-risk individuals. Evaluate and compare insulin resistance (IR) and β-cell dysfunction in individuals with normal glucose tolerance (NGT) and 1-hour post-load plasma glucose (1-h PG) ≥ 8.6 mmol/L versus < 8.6 mmol/L, as well as prediabetes based on IFG and/or IGT.Research design and methodsThis retrospective study included individuals at risk for diabetes who underwent an Oral Glucose Tolerance Test (OGTT), classified as having NGT or prediabetes according to ADA criteria. IR and β-cell dysfunction were assessed using the Matsuda index, insulinogenic index (IGI30), and oral disposition index (DI).ResultsAmong the 9,452 participants, 37.8% had NGT, and 62.2% were IFG or IGT in OGTT. Of the NGT group, 39.2% had a 1-h PG ≥ 8.6 mmol/L, with a higher mean age (53 vs. 47 years for those with 1-h PG < 8.6 mmol/L). Glucose and insulin curves showed that the NGT group with 1-h PG ≥ 8.6 mmol/L exhibited glucose profiles similar to those with isolated impaired fasting glucose (I-IFG), marked by elevated glucose, early insulin secretion impairment, and delayed insulin peaks. Older individuals (≥ 65 years) had higher glucose and a higher prevalence of abnormal 1-h PG but showed no significant differences in IR or β-cell dysfunction compared to younger individuals.ConclusionsA 1-h PG ≥ 8.6 mmol/L in individuals with NGT is associated with substantial β-cell dysfunction, highlight the value of incorporating 1-h PG measurement into diagnostic assessments for early detection of insulin secretion impairments across age groups.